Combined effect of various elastic loading conditions and aerobic bacterium Pseudoalteromonas sp. on the corrosion behavior of S32750 super duplex stainless steel. (March 2021) - Guo, Pushan; Moradi, Masoumeh; Yang, Lijing; Song, Zhenlun
Highlights: Both elastic loading and aerobic bacterium can aggravate the corrosion of SDSS. The effect of elastic loading and Pseudoalteromonas sp. is a nonlinear interaction. The condition of σ0.5s with Pseudoalteromonas sp. was much more harmful for SDSS. Abstract: The combined effect of various elastic loading conditions and aerobic bacterium Pseudoalteromonas sp. on the corrosion behavior of S32750 super duplex stainless steel was investigated using electrochemical and surface analysis methods. Our results show that the combined influence is a nonlinear relationship between both parameters. The corrosion rate of S32750 SDSS under the combined effect is higher than the sum of the corrosion rate under elastic loading and under aerobic bacterium. The loading condition of σ0.5s in the presence of Pseudoalteromonas sp. caused to more harmful effects than the loading of σ0.75s with bacteria.